Modified EVA (Ethylene Vinyl Acetate) and preparation method and application thereof

By adsorbing amino acids onto modified activated carbon and grafting them onto the EVA main chain, the problem of removing acetaldehyde impurities during the alcoholylation of ethylene-vinyl acetate copolymer is solved, and efficient removal of EVOH materials and strength improvement is achieved.

CN119798694APending Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510000335.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove acetaldehyde impurities during the alcoholylation process of ethylene-vinyl acetate copolymer (EVA), resulting in the coloring of EVOH materials and affecting application.

Method used

By adsorbing amino acids onto the modified activated carbon and grafting the modified activated carbon onto the EVA main chain, the amino acids are used to decompose acetaldehyde to remove acetaldehyde impurities.

Benefits of technology

It achieves efficient removal of acetaldehyde impurities, avoids yellowing of EVOH material, and improves the composite strength of EVOH.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses modified EVA (Ethylene Vinyl Acetate) as well as a preparation method and application thereof. According to the invention, physical adsorption of activated carbon is combined with chemical adsorption of amino acid, so that acetaldehyde in an EVA product is greatly reduced, the yellowing problem of an EVOH product caused by condensation of crotonaldehyde in a subsequent alcoholysis process is avoided, and meanwhile, the composite strength of EVOH is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ethylene-vinyl acetate copolymers, and specifically relates to a modified ethylene-vinyl acetate copolymer and a preparation method and application thereof. Background Art

[0002] EVOH is a random copolymer of ethylene-vinyl alcohol, which is composed of 15-45% mol% ethylene and 55-85% vinyl alcohol. EVOH has both the barrier properties of polyvinyl alcohol (PVA) and the processing properties of polyethylene (PE). It is widely used as one of the three major barrier resins along with polyvinylidene fluoride and polyamide. Ethylene-vinyl alcohol copolymer (EVOH) has excellent barrier properties to gases such as oxygen, transparency, oil resistance, non-chargeability, chemical corrosion resistance, weather resistance, printability, transparency, mechanical strength, etc., so it is widely used as a material for films, sheets, containers, etc.

[0003] Since vinyl alcohol cannot stably exist in the form of a monomer under normal conditions, EVOH can be prepared by the alcoholysis reaction of ethylene-vinyl acetate copolymer (EVA) prepared by the copolymerization of ethylene and vinyl acetate. As catalysts for the alcoholysis reaction of EVA, alkali catalysts such as sodium hydroxide, potassium hydroxide, alkali metal alcoholates, etc. are mainly used. EVOH contains hydrogen bonds, and the existence of intermolecular forces makes the materials prepared from EVOH have good barrier properties. In the entire preparation process of EVOH, the alcoholysis of EVA to prepare EVOH is a key step. The alcoholysis degree of EVOH determines its gas barrier properties. EVOH preferably used for food packaging, etc. has a high alcoholysis degree of more than 99%. Usually, alcoholysis uses a large amount of unrecycled strong bases such as sodium hydroxide and potassium hydroxide as catalysts and is carried out in alcohol solvents.

[0004] CN110139890A and CN115477798A disclose a copolymerization method of ethylene-vinyl acetate copolymer (EVA), describing that the polymerization rate reaches 60%, and a polymerization inhibitor such as a conjugated polyene is used for termination, which will result in a large amount of unpolymerized vinyl acetate in the reaction that needs to be eliminated. Vinyl acetate can be removed by adding an organic solvent such as methanol, and the mixed steam of the organic solvent such as methanol and the unreacted vinyl acetate monomer is evaporated together to remove the unreacted vinyl acetate monomer, but at this time, the unreacted vinyl acetate monomer will undergo an ester exchange side reaction with methanol under high temperature conditions to produce acetaldehyde.

[0005] CN109651557A discloses a method for preparing ethylene-vinyl alcohol copolymer, which uses sodium hydroxide, potassium hydroxide, sodium methoxide, sodium ethoxide and potassium methoxide as alkaline catalysts to prepare EVOH by alcoholysis of EVA in alcoholic solvents, and the use of a large number of alkaline catalysts will increase the difficulty of handling the three wastes; CN116003653A mentions that a large amount of methyl acetate will be produced during alcoholysis, and the forward progress of alcoholysis reaction will be affected, so during the reaction process, it is necessary to continuously supplement solvent or solvent vapor to take away the by-product methyl acetate through azeotropy, which undoubtedly requires a higher alcoholysis temperature and increases energy consumption. Alcoholysis reaction is in a high temperature, alkaline environment, under the condition of alcoholic solvents, it will accelerate the catalysis of unreacted vinyl acetate residues to produce acetaldehyde by transesterification, and acetaldehyde is further condensed to obtain unsaturated aldehydes such as crotonaldehyde, and the presence of such unsaturated aldehydes will cause EVOH to be colored, affecting subsequent applications, therefore, in the art, it is desirable to develop a method for removing acetaldehyde impurities during alcoholysis.

[0006] There are many aldehyde removal products on the market, such as activated carbon or diatom mud based on physical adsorption. Activated carbon is widely used in the field of impurity treatment due to its huge specific surface area, developed pore structure and strong adsorption capacity. Such products have an adsorption effect on aldehydes, but the adsorption capacity is limited, and after the adsorption reaches saturation, if it is not handled in time, it will desorb from the surface of the material again when the temperature rises. Therefore, it is necessary to find a new method for preparing EVOH by alcoholysis of EVA. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a modified EVA and its preparation method and application. The present invention adsorbs amino acids that can remove aldehydes onto activated carbon, and uses a silane coupling agent to modify and connect the activated carbon to the EVA main chain, which can effectively remove acetaldehyde impurities in the system, avoid yellowing of EVOH products, and improve the composite strength of EVOH products.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a modified EVA, comprising the following steps:

[0010] (1) Modification of activated carbon using aminosilane coupling agent or vinylsilane coupling agent;

[0011] (2) soaking the modified activated carbon in amino acids for sufficient adsorption to obtain modified activated carbon adsorbed with amino acids;

[0012] (3) Copolymerizing ethylene and vinyl acetate to obtain EVA by solution polymerization;

[0013] (4) Grafting silane coupling agent onto EVA to obtain modified EVA.

[0014] The specific steps of step (1) of the present invention include:

[0015] The aminosilane coupling agent or vinylsilane coupling agent is mixed with activated carbon, heat-treated under the protection of an inert atmosphere, and then washed and dried to obtain modified activated carbon.

[0016] Specifically, the aminosilane coupling agent can be selected from one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, anilinemethyltriethoxysilane, anilinemethyltrimethoxysilane, N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, 3-aminopropyl (diethoxy) methyl silane, and the added amount is 30wt%-50wt% of the activated carbon.

[0017] Specifically, the vinyl silane coupling agent can be selected from one or more of divinyldimethylsilane, triethoxyvinylsilane, vinyltrimethoxysilane, and vinylmethyldichlorosilane, and the added amount is 30wt%-50wt% of the activated carbon.

[0018] Specifically, the heat treatment temperature is 30-60° C., and the heat treatment time is 1-3 hours.

[0019] Specifically, the washing can be performed by shaking in a 30-60°C water bath constant temperature oscillator for 1-3 hours, in order to remove the remaining silane coupling agent;

[0020] Specifically, the present invention does not limit the drying conditions, that is, the drying purpose can be achieved, such as a drying temperature of 40-80° C. and a drying time of 5-10 hours.

[0021] Preferably, the activated carbon is subjected to activation treatment before modification, specifically: the activated carbon is activated at high temperature, treated with alkali, filtered, washed and then dried.

[0022] Specifically, the activated carbon is coconut shell activated carbon powder with a particle size of 100-600 meshes.

[0023] Specifically, the activated carbon is activated at 500-600°C for 4-5h, then soaked in alkaline solution, treated at 75-85°C for 3-4h, washed and dried at 40-80°C for 2-3h until the surface moisture is completely removed to obtain activated activated carbon.

[0024] In step (2) of the present invention, the activated carbon is immersed in amino acids for sufficient adsorption, and the amino acids can be selected from one or more of cysteine, arginine, glycine, lysine, histidine, phenylalanine or aspartic acid.

[0025] Specifically, the specific amount of the amino acid is not limited, and the modified activated carbon can be fully adsorbed by soaking in the amino acid.

[0026] In a preferred embodiment of the present invention, the adsorption operation can be performed using a collection adsorption frame and an adsorption extraction tube in accordance with the method of CN117771745B. Specifically, the adsorption extraction tube is filled with modified activated carbon and inserted into the amino acid collection adsorption frame for sufficient contact, thereby making it easier to adsorb the amino acids.

[0027] The modified activated carbon particles of step (1) are placed in an adsorption extraction tube. Preferably, the adsorption extraction tube is evenly provided with small holes, and the interior of the adsorption extraction tube contains amino / vinyl modified activated carbon particles.

[0028] Insert each adsorption extraction tube into the interior of the collection adsorption frame so that the activated carbon particles inside each adsorption extraction tube are in full contact with the liquid in the collection adsorption frame, and the amino acids inside are fully adsorbed and treated. Take out the modified activated carbon particles adsorbed with amino acids, put them into methanol solvent and heat them to obtain the amino-modified activated carbon solution adsorbed with amino acids.

[0029] Preferably, the activated carbon is immersed in the amino acid for 3-5 hours to achieve sufficient adsorption.

[0030] Preferably, the specific steps of step (3) of the present invention are:

[0031] Vinyl acetate monomer, initiator, ethylene monomer and solvent are mixed as raw materials, and EVA is prepared through in-vessel replacement, initial charging, polymerization reaction and blowing out residual monomers.

[0032] Specifically, the in-kettle replacement refers to replacing the reaction kettle with inert gas and ethylene; the initial charging is to add the solvent into the reaction kettle and stir; the polymerization reaction is to add vinyl acetate monomer and ethylene monomer into the reaction kettle after the initial charging, and when the temperature in the kettle is 40-80°C, add the initiator to start the reaction.

[0033] In a specific embodiment, the preparation of EVA in step (3) comprises the following steps:

[0034] 1) Replacement in the kettle

[0035] Replace the reactor with 5-10 bar N2 for multiple times, and then replace it with 5-10 bar ethylene for multiple times, each replacement lasting 5-9 minutes;

[0036] 2) Initial feeding

[0037] Add vinyl acetate, solvent and initiator into the reaction kettle, stir at 60-180 rpm for 5-10 min at room temperature to make the mixture uniform;

[0038] 3) Polymerization reaction

[0039] Ethylene monomer is introduced, and the pressure is controlled at 10-60 bar. When the temperature in the autoclave reaches 40-80°C, the timing is started. After 2.5-8.0 hours of reaction, the reaction is terminated, the introduction of ethylene is stopped, the temperature is lowered, the pressure is released, and the polymerization product is obtained.

[0040] 4) Blow out the remaining orders

[0041] A polymerization inhibitor is added to the polymerization reaction product, and the mixture is stirred. Then, unreacted vinyl acetate monomer is removed by heating while adding methanol to obtain a methanol resin solution of ethylene-vinyl acetate copolymer.

[0042] Preferably, in step 2), vinyl acetate and solvent are added in a mass ratio of 6:1 to 3:1, and the initiator is 1500-3000 ppm. Preferably, deoxygenation is performed in advance before adding to the reactor. Specifically, vinyl acetate monomer, solvent and initiator are pre-mixed, and nitrogen is introduced while stirring to fully replace the mixture so that the oxygen content in the system is less than 1.0×10 -3 mol / L and then added into the reactor.

[0043] Specifically, the solvent in step 2) is an alcohol solvent having 1 to 4 carbon atoms, such as methanol, ethanol, etc.

[0044] Specifically, the initiator in step 2) is azobisisobutyronitrile.

[0045] Specifically, in step 3), ethylene monomer is introduced to allow ethylene and vinyl acetate to undergo polymerization reaction at a molar ratio of 28-35:65-72.

[0046] Specifically, after the reaction in step 3) is completed, the temperature is preferably lowered to below 35° C., and the pressure is reduced to 5-8 bar before discharging.

[0047] Specifically, in step 4), the polymerization inhibitor is preferably hydroquinone or p-benzoquinone; the amount of the polymerization inhibitor is 0.1-0.5 wt % of the polymerization reaction product.

[0048] Specifically, in step 4), the temperature of the heating devolatilization is 40-60° C. and the time is 8-16 hours.

[0049] In the preparation method of the modified EVA of the present invention, step (4) of grafting EVA with a silane coupling agent comprises the following steps:

[0050] A. Adding the main monomer: adding the modified activated carbon solution obtained in step (2) which is pre-dissolved in a solvent to the methanol resin solution of ethylene-vinyl acetate copolymer;

[0051] B. Adding photoinitiator: adding chemical crosslinking agent and photoinitiator to carry out polymerization reaction to obtain modified EVA solution.

[0052] Specifically, in step A, the concentration of the ethylene-vinyl acetate copolymer methanol resin solution is 20-30wt%; the concentration of the modified activated carbon solution is 5-30wt%.

[0053] Specifically, the solvent in step A is an alcohol solvent having 1 to 4 carbon atoms, such as methanol, ethanol, etc.

[0054] Specifically, the process of step A is controlled at 70-90° C. and pH 2-6.

[0055] Specifically, the photoinitiator in step B is a benzoin ether or benzophenone photoinitiator.

[0056] Specifically, the chemical crosslinking agent in step B is tert-butyl peroxybenzoate or tert-butyl peroxy 2-ethylhexyl carbonate.

[0057] Specifically, in step B, the polymerization reaction temperature is 70-80° C., and the reaction time is 60-80 min.

[0058] Specifically, in the modified EVA solution, the methanol resin solution of ethylene-vinyl acetate copolymer accounts for 65-70wt%, the chemical crosslinking agent accounts for 1.5-3wt%, the photoinitiator accounts for 0.1-0.5wt%, the modified activated carbon solution accounts for 5-10wt%, and the rest is solvent.

[0059] In a second aspect, the present invention provides a method for preparing EVOH by alcoholysis of the modified EVA, the specific steps of which are:

[0060] A catalyst is added to the modified EVA solution to carry out alcoholysis reaction to prepare a solution containing ethylene-vinyl alcohol copolymer, and water is added to precipitate and shape the solution, and the solution is washed and filtered, melt-extruded and granulated, and dried to obtain EVOH.

[0061] Specifically, the catalyst is one or more of sodium hydroxide and potassium hydroxide, and the molar ratio of the catalyst to the vinyl acetate monomer unit in the ethylene-vinyl acetate copolymer is 0.001-1, preferably 0.01-1, and more preferably 0.01-0.1.

[0062] Specifically, the alcoholysis reaction can be carried out in an organic solvent, which can be the same as or different from the organic solvent used in the solution polymerization process, preferably the same as the organic solvent used in the solution polymerization process, that is, an alcohol solvent with 1-4 carbon atoms, such as methanol, ethanol, etc.

[0063] Specifically, the reaction temperature of the alcoholysis reaction is 30-80° C., preferably 40-70° C., and the alcoholysis rate of the polymer is above 99%, preferably above 99.5%.

[0064] Specifically, during the polymer precipitation forming process, the temperature of water is 1-50°C, preferably 20-40°C.

[0065] Specifically, the washing detergent is methanol, or a mixed solution of methanol and water. Specifically, the washing temperature is 10-60°C, preferably 20-50°C. The washing time can be 1-6 hours. This process can wash away low molecular weight polymers in the polymer and reduce the negative impact of oligomers on performance. When the conductivity of the washing water is lower than 10us / cm, the washing is considered qualified.

[0066] Specifically, the melt extrusion granulation is carried out in a screw extruder or a kneader, preferably in a screw extruder, and more preferably in a twin-screw extruder.

[0067] Specifically, during the melt extrusion process, the resin may be in a water-containing state, with a water content of 10-60%, preferably 30-40%, and the processing temperature of the melt extrusion is 60-130° C., preferably 80-110° C.; the granulation adopts strand pelletizing or underwater pelletizing.

[0068] Specifically, the polymer particles obtained by granulation are dried at a temperature of 50-160°C, preferably 60-150°C, and more preferably 70-120°C.

[0069] Specifically, the drying process can use a static dryer or a dynamic dryer, such as a belt dryer, a tower dryer, a fluidized bed dryer, or a combination of a static dryer and a dynamic dryer, preferably a dynamic dryer first and then a static dryer. Through the drying process, the resin moisture content is finally dried to less than 0.5wt%, preferably less than 0.3wt%.

[0070] Specifically, the extrusion granulation process is as follows: adding the dried granules into a twin-screw extruder, with the temperature of the screw extruder being 150-180° C. and the rotation speed being 20-30 rpm, extruding, air-cooling, drying and granulating to obtain EVOH products.

[0071] Compared with the prior art, the present invention has the following beneficial effects:

[0072] The present invention modifies activated carbon by a silane coupling agent and grafts it onto the polymer EVA. While improving the strength of the polymer, the activated carbon is used to collect aldehyde substances generated during the polymerization process, and then the aldehyde substances are decomposed by the internal amino acids, thereby removing the aldehyde impurities generated during the polymerization process and avoiding the generation of impurities such as crotonaldehyde during further alcoholysis. The acetaldehyde content of the product improved by the present invention is reduced, and the mechanical properties and anti-yellowing properties are improved to a certain extent. DETAILED DESCRIPTION

[0073] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0074] Example 1

[0075] S1. Take a certain amount of coconut shell activated carbon powder (particle size 300 mesh), add 30wt% of N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane based on the activated carbon mass, heat treat at 30°C for 2h under inert atmosphere protection, then oscillate in a water bath constant temperature oscillator at 40°C for 1h, then filter and dry to obtain amino modified activated carbon;

[0076] S2. The activated carbon particles in the adsorption extraction tube are fully contacted with the glycine in the collection adsorption frame for 5 hours to fully adsorb the glycine inside, and the modified activated carbon particles adsorbed with glycine are taken out and placed in methanol for heating to obtain an amino modified activated carbon solution.

[0077] S3, EVA polymerization reaction: including the following steps:

[0078] 1) Replacement in the kettle

[0079] Replace with 5 bar of N2 twice, and then replace with 5 bar of ethylene twice, each replacement lasting 5 minutes;

[0080] 2) Initial feeding

[0081] Add vinyl acetate, methanol at a mass ratio of 5:1 and 1500 ppm of AIBN into the reactor, and stir at 180 rpm for 5 min at room temperature to make the mixture uniform;

[0082] 3) Polymerization reaction

[0083] Ethylene monomer was introduced (the molar ratio of ethylene to vinyl acetate was controlled to be 32:68), the pressure was controlled to be 50 bar, the timing was started when the temperature in the autoclave reached 60°C, the reaction was terminated after 3 hours of reaction, the ethylene inlet valve was closed, the temperature was lowered to below 35°C, and the pressure was released to 6.0 bar to obtain the polymerization product;

[0084] 4) Blow out the remaining orders

[0085] A polymerization inhibitor (hydroquinone) equivalent to 0.1 wt% of the polymerization product was added to the polymerization reaction product, calculated as a weight percentage, and the materials in the kettle were heated while methanol was introduced. The stirring was started at 200 rpm for 30 minutes, and the unreacted vinyl acetate monomer was removed by devolatilization to obtain a 25 wt% methanol resin solution of ethylene-vinyl acetate copolymer.

[0086] S4, grafting silane coupling agent onto EVA: adding methanol to a stirred reactor, stirring at 80 rpm, gradually adding methanol resin solution of ethylene-vinyl acetate copolymer at 80°C and pH 4.5, slowly dripping 10 wt% modified activated carbon solution pre-dissolved in methanol; stirring at 150 rpm, mixing for 30 min; adding chemical crosslinking agent and initiator: adding tert-butyl peroxybenzoate and benzoin ethyl ether respectively, wherein the mass ratio of methanol resin solution of ethylene-vinyl acetate copolymer, modified activated carbon solution, tert-butyl peroxybenzoate and benzoin ethyl ether is 70:5:1.5:0.5. Polymerization reaction was carried out at 70°C for 60 min to obtain modified EVA solution, and the acetaldehyde content was tested.

[0087] S5, preparation of EVOH: adding sodium hydroxide at a molar ratio of 0.05 to the vinyl acetate monomer unit in the ethylene-vinyl acetate copolymer to the modified EVA solution, preparing the EVA resin to have a solid content of 30%, alcoholyzing at 60°C for 4 hours, with an alcoholysis degree of more than 99.8%, then settling in 25°C water, washing for 5 hours, and the conductivity of the washing water is less than 10us / cm. Extruding the resin with a water content of 30wt% in a twin-screw extruder at 110°C for granulation, and drying at 100°C to a water content of <0.3wt%, to obtain EVOH.

[0088] The dried pellets were continuously added to the extruder and molded at 210°C for 15 minutes, cooled for 10 minutes, and placed at 20°C for 10 hours after molding. The tensile strength, elongation at break, and color difference b value of the film were measured.

[0089] Example 2

[0090] S1. Take a certain amount of coconut shell activated carbon powder (particle size 300 mesh), add 50wt% of N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane to the activated carbon, heat treat at 40°C for 1h under inert atmosphere, and then oscillate in a 40°C water bath constant temperature oscillator for 1h, then filter and dry to obtain amino modified activated carbon;

[0091] S2, fully contacting the activated carbon particles in the adsorption extraction tube with the glycine in the collection adsorption frame for 5 hours to fully adsorb the glycine inside, and taking out the modified activated carbon particles adsorbing glycine.

[0092] The mixture was placed in methanol and heated to obtain an amino-modified activated carbon solution.

[0093] S3, EVA polymerization reaction: including the following steps:

[0094] 1) Replacement in the kettle

[0095] Replace with 5 bar of N2 twice, and then replace with 5 bar of ethylene twice, each replacement lasting 5 minutes;

[0096] 2) Initial feeding

[0097] Add vinyl acetate, methanol at a mass ratio of 5:1 and 1500ppm of AIBN into the reactor, and stir at 150rpm for 8min at room temperature to make the mixture uniform;

[0098] 3) Polymerization reaction

[0099] Ethylene monomer was introduced (the molar ratio of ethylene to vinyl acetate was controlled to be 32:68), the pressure was controlled to be 50 bar, the timing was started when the temperature in the autoclave reached 60°C, the reaction was terminated after 3.5 hours of reaction, the ethylene inlet valve was closed, the temperature was lowered to below 35°C, and the pressure was released to 6.0 bar to obtain the polymerization product;

[0100] 4) Blow out the remaining orders

[0101] A polymerization inhibitor (hydroquinone) equivalent to 0.1wt% of the polymerization product is added to the polymerization reaction product, calculated as a weight percentage, and methanol is introduced while the material in the kettle is heated. The stirring is turned on at 200rpm for 30 minutes, and the unreacted vinyl acetate monomer is removed by devolatilization to obtain a methanol resin solution of ethylene-vinyl acetate copolymer with a mass fraction of 20%.

[0102] S4, grafting silane coupling agent onto EVA: adding methanol to a stirred reactor, stirring at 80 rpm, gradually adding methanol resin solution of ethylene-vinyl acetate copolymer at 80°C and pH 4.5, slowly dripping 20wt% modified activated carbon solution pre-dissolved in methanol; stirring at 150 rpm, mixing for 30 min; adding chemical crosslinking agent and initiator: adding tert-butyl peroxybenzoate and benzoin ethyl ether respectively, wherein the mass ratio of methanol resin solution of ethylene-vinyl acetate copolymer, modified activated carbon solution, tert-butyl peroxybenzoate and benzoin ethyl ether is 68:5:1.5:0.3. Polymerization reaction was carried out at 70°C for 60 min to obtain modified EVA solution, and the acetaldehyde content was tested.

[0103] S5, preparation of EVOH: adding sodium hydroxide at a molar ratio of 0.08 to the vinyl acetate monomer unit in the ethylene-vinyl acetate copolymer to the modified EVA solution, preparing the EVA resin to have a solid content of 30%, alcoholyzing at 60°C for 4 hours, with an alcoholysis degree of more than 99.8%, then settling in 30°C water, washing for 5 hours, and the conductivity of the washing water is less than 10us / cm. The resin with a water content of 30% is extruded and granulated at 110°C in a twin-screw extruder, and dried at 100°C to a water content of <0.3%.

[0104] The dried pellets were continuously added to the extruder and molded at 210°C for 15 minutes, cooled for 10 minutes, and placed at 20°C for 10 hours after molding. The tensile strength, elongation at break, and color difference b value of the film were measured.

[0105] Example 3

[0106] S1. Take a certain amount of coconut shell activated carbon powder (particle size 300 mesh), put it in a beaker, add 30wt% vinylmethyldichlorosilane, heat treat it at 40°C for 2h under inert atmosphere protection, then oscillate in a 40°C water bath constant temperature oscillator for 1h, then filter and dry to obtain vinyl modified activated carbon;

[0107] S2. The activated carbon particles in the adsorption extraction tube are fully contacted with the lysine in the collection adsorption frame for 5 hours to fully adsorb the lysine inside, and the modified activated carbon particles adsorbed with lysine are taken out and placed in methanol for heating to obtain an amino modified activated carbon solution.

[0108] S3, EVA polymerization reaction: including the following steps:

[0109] 1) Replacement in the kettle

[0110] Replace with 5 bar of N2 twice, and then replace with 5 bar of ethylene twice, each replacement lasting 5 minutes;

[0111] 2) Initial feeding

[0112] Add vinyl acetate, methanol at a mass ratio of 5:1 and 2000 ppm of AIBN into the reactor, and stir at 180 rpm for 5 min at room temperature to make the mixture uniform;

[0113] 3) Polymerization reaction

[0114] Ethylene monomer was introduced (the molar ratio of ethylene to vinyl acetate was controlled to be 32:68), the pressure was controlled to be 50 bar, the timing was started when the temperature in the autoclave reached 60°C, the reaction was terminated after 3 hours of reaction, the ethylene inlet valve was closed, the temperature was lowered to below 35°C, and the pressure was released to 6.0 bar to obtain the polymerization product;

[0115] 4) Blow out the remaining orders

[0116] A polymerization inhibitor (hydroquinone) equivalent to 0.1wt% of the polymerization product is added to the polymerization reaction product, calculated as a weight percentage, and methanol is introduced while the material in the kettle is heated. The stirring is turned on at 200rpm for 30 minutes, and the unreacted vinyl acetate monomer is removed by devolatilization to obtain a methanol resin solution of ethylene-vinyl acetate copolymer with a mass fraction of 25%.

[0117] S4, grafting silane coupling agent onto EVA: adding methanol to a stirred reactor, stirring at 80 rpm, gradually adding methanol resin solution of ethylene-vinyl acetate copolymer at 80°C and pH 4.5, slowly dripping 15wt% modified activated carbon solution pre-dissolved in solvent; stirring at 150 rpm, mixing for 30 min; adding chemical crosslinking agent and initiator: adding tert-butyl peroxybenzoate and benzoin ethyl ether respectively, wherein the mass ratio of methanol resin solution of ethylene-vinyl acetate copolymer, modified activated carbon solution, tert-butyl peroxybenzoate and benzoin ethyl ether is 65:10:1.5:0.5. Carry out polymerization reaction at 75°C for 60 min to obtain modified EVA solution, and test the acetaldehyde content.

[0118] S5. Preparation of EVOH: Add sodium hydroxide in a molar ratio of 0.05 to the vinyl acetate monomer unit in the ethylene-vinyl acetate copolymer to the modified EVA solution, prepare the EVA resin to have a solid content of 30%, perform alcoholysis at 60°C for 4 hours, and achieve an alcoholysis degree of more than 99.8%, then settle in water at 25°C, wash for 5 hours, and achieve a conductivity of the washing water of less than 10us / cm. Extrude and granulate the resin having a water content of 30% at 110°C in a twin-screw extruder, and dry at 100°C to a water content of <0.3%.

[0119] The dried pellets were continuously added to the extruder and molded at 210°C for 15 minutes, cooled for 10 minutes, and placed at 20°C for 10 hours after molding. The tensile strength, elongation at break, and color difference b value of the film were measured.

[0120] Comparative Example 1

[0121] Take a certain amount of diatom mud powder (particle size 300 mesh), put it in a beaker, add 30wt% N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, heat treat it at 30℃ for 2h under inert atmosphere, and then oscillate in a 40℃ water bath constant temperature oscillator for 1h, then filter and dry to obtain amino modified activated carbon; the activated carbon particles inside the adsorption extraction tube are fully contacted with the glycine in the collection adsorption frame for 5h, and the glycine inside is fully adsorbed, and the modified activated carbon particles adsorbed with glycine are taken out, and put into methanol and heated to obtain amino modified activated carbon solution.

[0122] S3, EVA polymerization reaction: including the following steps:

[0123] 1) Replacement in the kettle

[0124] Replace with 5 bar of N2 twice, and then replace with 5 bar of ethylene twice, each replacement lasting 5 minutes;

[0125] 2) Initial feeding

[0126] Add vinyl acetate, methanol at a mass ratio of 5:1 and 1500 ppm of AIBN into the reactor, and stir at 180 rpm for 5 min at room temperature to make the mixture uniform;

[0127] 3) Polymerization reaction

[0128] Ethylene monomer was introduced (the molar ratio of ethylene to vinyl acetate was controlled to be 32:68), the pressure was controlled to be 50 bar, the timing was started when the temperature in the autoclave reached 60°C, the reaction was terminated after 3 hours of reaction, the ethylene inlet valve was closed, the temperature was lowered to below 35°C, and the pressure was released to 6.0 bar to obtain the polymerization product;

[0129] 4) Blow out the remaining orders

[0130] A polymerization inhibitor (hydroquinone) equivalent to 0.1wt% of the polymerization product is added to the polymerization reaction product, calculated as a weight percentage, and methanol is introduced while the material in the kettle is heated. The stirring is turned on at 200rpm for 30 minutes, and the unreacted vinyl acetate monomer is removed by devolatilization to obtain a methanol resin solution of ethylene-vinyl acetate copolymer with a mass fraction of 25%.

[0131] S4, grafting silane coupling agent onto EVA: adding methanol to a stirred reactor, stirring at 80 rpm, gradually adding methanol resin solution of ethylene-vinyl acetate copolymer at 80°C and pH 4.5, slowly dripping 10 wt% modified activated carbon solution pre-dissolved in solvent; stirring at 150 rpm, mixing for 30 min; adding chemical crosslinking agent and initiator: adding tert-butyl peroxybenzoate and benzoin ethyl ether in batches, wherein the mass ratio of methanol resin solution of ethylene-vinyl acetate copolymer, modified activated carbon solution, tert-butyl peroxybenzoate and benzoin ethyl ether is 70:5:1.5:0.5. Carry out polymerization reaction at 70°C for 60 min to obtain modified EVA solution, and test the acetaldehyde content.

[0132] To the modified EVA solution, 0.05 molar ratio of sodium hydroxide relative to the vinyl acetate monomer unit in the ethylene-vinyl acetate copolymer was added, and the EVA resin was prepared to have a solid content of 30%. The solution was subjected to alcoholysis at 60°C for 4 hours, with an alcoholysis degree of more than 99.8%. The solution was then precipitated in water at 25°C and washed for 5 hours. The conductivity of the washing water was less than 10us / cm. The resin with a water content of 30wt% was extruded and granulated at 110°C in a twin-screw extruder, and dried at 100°C to a water content of <0.3wt%, to obtain EVOH.

[0133] The dried pellets were continuously added to the extruder and molded at 210°C for 15 minutes, cooled for 10 minutes, and placed at 20°C for 10 hours after molding. The tensile strength, elongation at break, and color difference b value of the film were measured.

[0134] Comparative Example 2

[0135] EVA polymerization reaction: including the following steps:

[0136] 1) Replacement in the kettle

[0137] Replace with 5 bar of N2 twice, and then replace with 5 bar of ethylene twice, each replacement lasting 5 minutes;

[0138] 2) Initial feeding

[0139] Add vinyl acetate, methanol at a mass ratio of 5:1 and 1500 ppm of AIBN into the reactor, and stir at 180 rpm for 5 min at room temperature to make the mixture uniform;

[0140] 3) Polymerization reaction

[0141] Ethylene monomer was introduced (the molar ratio of ethylene to vinyl acetate was controlled to be 32:68), the pressure was controlled to be 50 bar, the timing was started when the temperature in the autoclave reached 60°C, the reaction was terminated after 3 hours of reaction, the ethylene inlet valve was closed, the temperature was lowered to below 35°C, and the pressure was released to 6.0 bar to obtain the polymerization product;

[0142] 4) Blow out the remaining orders

[0143] A polymerization inhibitor (hydroquinone) equivalent to 0.1 wt% of the polymerization product was added to the polymerization reaction product, and stirring was started at 200 rpm for 30 minutes. Then, methanol was introduced while the materials in the kettle were heated to remove unreacted vinyl acetate monomer by devolatilization to obtain a 25 wt% methanol resin solution of ethylene-vinyl acetate copolymer.

[0144] Grafting silane coupling agent onto EVA: Add methanol into a stirred reactor, start stirring, stirring speed 80rpm, gradually add methanol resin solution of ethylene-vinyl acetate copolymer at 80℃, pH 4.5; stirring speed 150rpm, mixing time 30min; Add chemical crosslinker and initiator: add tert-butyl perbenzoate and benzoin ethyl ether respectively, wherein the mass ratio of methanol resin solution of ethylene-vinyl acetate copolymer, tert-butyl perbenzoate and benzoin ethyl ether is 70:1.5:0.5. Carry out polymerization reaction at 70℃, reaction time 60min, obtain modified EVA solution, and test acetaldehyde content.

[0145] A methanol solution containing sodium hydroxide at a molar ratio of 0.05 to the vinyl acetate monomer unit in the ethylene-vinyl acetate copolymer was added to the modified EVA solution, and the EVA resin was prepared to have a solid content of 30%. The solution was subjected to alcoholysis at 60°C for 4 hours, with an alcoholysis degree of more than 99.8%. The solution was then precipitated in water at 25°C and washed for 5 hours. The conductivity of the washing water was less than 10us / cm. The resin with a water content of 30wt% was extruded and granulated at 110°C in a twin-screw extruder, and dried at 100°C to a water content of <0.3%.

[0146] The dried pellets were continuously added to the extruder and molded at 210°C for 15 minutes, cooled for 10 minutes, and placed at 20°C for 10 hours after molding. The tensile strength, elongation at break, and color difference b value of the film were measured.

[0147] Comparative Example 3

[0148] Take a certain amount of coconut shell activated carbon powder (particle size 300 mesh), add 30wt% of N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane to the activated carbon, heat treat it at 30℃ for 2h under inert atmosphere, then oscillate in a 40℃ water bath constant temperature oscillator for 1h, then filter and dry to obtain amino-modified activated carbon.

[0149] EVA polymerization reaction: including the following steps:

[0150] 1) Replacement in the kettle

[0151] Replace with 5 bar of N2 twice, and then replace with 5 bar of ethylene twice, each replacement lasting 5 minutes;

[0152] 2) Initial feeding

[0153] Add vinyl acetate, methanol at a mass ratio of 5:1 and 1500 ppm of AIBN into the reactor, and stir at 180 rpm for 5 min at room temperature to make the mixture uniform;

[0154] 3) Polymerization reaction

[0155] Ethylene monomer was introduced (the molar ratio of ethylene to vinyl acetate was controlled to be 32:68), the pressure was controlled to be 50 bar, the timing was started when the temperature in the autoclave reached 60°C, the reaction was terminated after 3 hours of reaction, the ethylene inlet valve was closed, the temperature was lowered to below 35°C, and the pressure was released to 6.0 bar to obtain the polymerization product;

[0156] 4) Blow out the remaining orders

[0157] A polymerization inhibitor (hydroquinone) equivalent to 0.1 wt% of the polymerization product was added to the polymerization reaction product, and stirring was started at 200 rpm for 30 minutes. Then, methanol was introduced while the materials in the kettle were heated to remove unreacted vinyl acetate monomers by devolatilization to obtain a methanol resin solution of ethylene-vinyl acetate copolymer.

[0158] Grafting silane coupling agent onto EVA: Add methanol to a stirred reactor, start stirring, stirring speed 80rpm, gradually add methanol resin solution of ethylene-vinyl acetate copolymer at 80℃, pH 4.5, slowly drop 10wt% modified activated carbon solution pre-dissolved in solvent; stirring speed 150rpm, mixing time 30min; Add chemical crosslinker and initiator: add tert-butyl perbenzoate and benzoin ethyl ether respectively, wherein the mass ratio of methanol resin solution of ethylene-vinyl acetate copolymer, modified activated carbon solution, tert-butyl perbenzoate and benzoin ethyl ether is 70:5:1.5:0.5. Carry out polymerization reaction at 70℃, reaction time 60min, obtain modified EVA solution, and test acetaldehyde content.

[0159] To the modified EVA solution, 0.05 molar ratio of sodium hydroxide relative to the vinyl acetate monomer unit in the ethylene-vinyl acetate copolymer was added, and the EVA resin was prepared to have a solid content of 30%. The solution was subjected to alcoholysis at 60°C for 4 hours, with an alcoholysis degree of more than 99.8%. The solution was then precipitated in water at 25°C and washed for 5 hours. The conductivity of the washing water was less than 10us / cm. The resin with a water content of 30% was extruded and granulated at 110°C in a twin-screw extruder, and dried at 100°C to a water content of <0.3wt%, to obtain EVOH.

[0160] The dried pellets were continuously added to the extruder and molded at 210°C for 15 minutes, cooled for 10 minutes, and placed at 20°C for 10 hours after molding. The tensile strength, elongation at break, and color difference b value of the film were measured.

[0161] The following are the results of the acetaldehyde content of EVA prepared in Examples 1-3 and Comparative Examples 1-3, the mechanical properties of EVOH, and the degree of yellowing:

[0162] Table 1 Test results

[0163] performance Tensile strength, MPa Elongation at break, % Color difference b value Acetaldehyde content Example 1 54.2 13.3 0.48 15ppm Example 2 51.3 11.8 0.53 20ppm Example 3 57.6 14.8 0.58 30ppm Comparative Example 1 47.9 10.2 0.57 25ppm Comparative Example 2 40.6 9.6 0.73 67ppm Comparative Example 3 45.9 10.4 0.64 45ppm

[0164] The tensile strength and elongation at break are tested in accordance with “GB / T 1040.2-2006 Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics”.

[0165] The color difference is measured by a colorimeter. The color difference b value mainly represents the difference between yellow and blue. The higher the value, the more yellowish it is, and the lower the value, the more bluish it is. Strengthen the anti-yellowing test. The test conditions are: 200℃×2 hours. Test the visible light transmittance and color difference b value of the material.

[0166] The acetaldehyde content was determined by headspace gas chromatography. A standard curve was drawn using acetaldehyde standards. The measured results were compared with the standard curve, and the peak area ratio was calculated to determine the final result.

[0167] By comparing Example 1 and Comparative Example 1, it can be seen that activated carbon has a better effect on removing acetaldehyde in EVA products than diatom mud, while the tensile strength and elongation at break are improved, and the color difference b value is low.

[0168] It can be seen from Examples 1-3 and Comparative Example 2 that the activated carbon combined with amino acids achieves a good removal effect on acetaldehyde in EVA, while the tensile strength and elongation at break are improved, and the color difference b value is low.

[0169] It can be seen from Example 1 and Comparative Example 3 that the physical adsorption of activated carbon modified by siloxane alone cannot achieve a good removal effect on acetaldehyde in EVA products.

[0170] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a modified EVA, comprising the following steps: (1) Modification of activated carbon using aminosilane coupling agent or vinylsilane coupling agent; (2) adsorbing amino acids on the modified activated carbon to obtain modified activated carbon adsorbing amino acids; (3) Copolymerizing ethylene and vinyl acetate to obtain EVA by solution polymerization; (4) Grafting silane coupling agent onto EVA to obtain modified EVA.

2. The method according to claim 1, characterized in that: The aminosilane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, anilinemethyltriethoxysilane, anilinemethyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldimethoxysilane, and 3-aminopropyl (diethoxy)methylsilane; And / or, the vinyl silane coupling agent is selected from one or more of vinyl trimethoxy silane, divinyl dimethyl silane, triethoxy vinyl silane, and vinyl methyl dichloro silane.

3. The method according to claim 1, wherein step (1) comprises mixing an aminosilane coupling agent or a vinylsilane coupling agent with activated carbon, performing a heat treatment under an inert atmosphere, and then washing and drying to obtain modified activated carbon.

4. The method according to claim 3, characterized in that The heat treatment temperature in step (1) is 30-60° C. and the heat treatment time is 1-3 h.

5. The method according to claim 1 or 3, characterized in that: The activated carbon in step (1) is coconut shell activated carbon powder with a particle size of 100-600 meshes.

6. The method according to claim 1, characterized in that In step (2), the modified activated carbon is immersed in amino acids for sufficient adsorption; Preferably, the amino acid is selected from one or more of cysteine, arginine, glycine, lysine, histidine, phenylalanine or aspartic acid.

7. The method according to claim 1, characterized in that Step (3) specifically comprises: mixing vinyl acetate monomer, initiator, ethylene monomer and solvent as raw materials, and preparing EVA through in-vessel replacement, initial charging, polymerization reaction and blowing out residual monomers; Preferably, the replacement in the reactor is to replace the reactor with inert gas and ethylene multiple times respectively; Preferably, the polymerization temperature is 40-80°C and the pressure is 10-60 bar.

8. The method according to claim 7, characterized in that The solvent is an alcohol having 1 to 4 carbon atoms, preferably methanol or ethanol; Preferably, the initiator is azobisisobutyronitrile, and the amount of the initiator is 1500-3000ppm; Preferably, the molar ratio of ethylene to vinyl acetate is 28-35:65-72.

9. The method according to claim 1, characterized in that: Step (4) grafting EVA with a silane coupling agent comprises the following steps: A. Adding the main monomer: adding the modified activated carbon solution obtained in step (2) which is pre-dissolved in a solvent to the methanol resin solution of ethylene-vinyl acetate copolymer; B. Adding photoinitiator: adding chemical crosslinking agent and photoinitiator to carry out polymerization reaction to obtain modified EVA solution; Preferably, in step B, the chemical crosslinking agent is tert-butyl peroxybenzoate or tert-butyl peroxy 2-ethylhexyl carbonate; the photoinitiator is a benzoin ether or benzophenone photoinitiator; Preferably, in step B, the polymerization reaction temperature is 70-80° C. and the reaction time is 60-80 min.

10. A method for preparing EVOH by alcoholysis of modified EVA, characterized in that: The specific steps are: adding a catalyst to the modified EVA solution prepared by the method according to any one of claims 1 to 9 to carry out alcoholysis reaction to prepare a solution containing ethylene-vinyl alcohol copolymer, adding water to precipitate and shape, washing and filtering, melt-extruding and granulating, and drying to obtain EVOH; Preferably, the alcoholysis temperature is 30-80°C.

Citation Information

Patent Citations

  • Method for preparing ethylene-vinyl alcohol copolymer

    CN109651557A

  • Ethylene-vinyl alcohol copolymer composition pellets and method for producing ethylene-vinyl alcohol copolymer composition pellets

    CN110139890A

  • Ethylene-vinyl alcohol copolymer resin composition, ethylene-vinyl alcohol copolymer film formed therefrom, and multilayer structure comprising same

    CN115477798A

  • Preparation method of polyethylene-vinyl alcohol resin and product obtained by preparation method

    CN116003653A

  • A device for purifying amino acids from organisms and a method of using the same

    CN117771745B